Effects of workload level on the timing of concentric-eccentric contractions during cycling - Lanferdini, F. J.; Bini, R. R.; Vaz, M. A. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The mechanical energy required to drive the cranks during cycling depends on concentric and eccentric muscle actions. However, no study to date provided clear evidence on how workload levels affect concentric and eccentric muscle actions during cycling. Therefore, the aim of this study was to investigate the workload effects on the timing of lower limb concentric and eccentric muscle actions, and on joint power production. METHODS: Twenty-one cyclists participated in the study. At the first session, maximal power output (POmax) and power output at the first (POVT1) and second (POVT2) ventilatory thresholds were determined during an incremental cycling test. At the second session, cyclists performed three trials (2 min/each) in the workloads determined from their POmax, POVT1 and POVT2, acquiring data of lower limb muscle activation, pedal forces and kinematics. Concentric and eccentric timings were computed from muscles` activations and muscle-tendon unit excursions along with hip, knee and ankle joints` power production. RESULTS: Longer rectus femoris eccentric activation (62%), vastus medialis concentric (66%) and eccentric activation (26%), and biceps femoris concentric (29%) and eccentric (133%) activation at POmax were observed compared to POVT1. Longer positive (12%) and shorter negative (12%) power were observed at the knee joint for POmax compared to POVT1. CONCLUSIONS: We conclude that, to sustain higher workload levels, cyclists improved the timing of power transmission from the hip to the knee joint via rectus femoris eccentric, vastus medialis concentric and eccentric and biceps femoris concentric and eccentric contractions.